Beamforming in the Generation of Range-Time-Dependent Orbital Angular Momentum Based on the Circular Frequency Diverse Array - Ge, Jiaang; Xie , Junwei (Frontiers in Physics, 2022)
In this article, we combine the frequency diverse array (FDA) with the vortex electromagnetic wave theory and propose a beamforming method in the generation of range-time-dependent orbital angular momentum (OAM) based on the circular FDA (CFDA). First, we establish a CFDA-based OAM-generating structure, based on which the feasibility of CFDA to generate OAM is verified. Then, we analyze the range-time-dependent characteristics of the generated OAM. Furthermore, concerning the field of radar imaging and target detection, we investigate beamforming with the CFDA-based OAM. Two main issues are addressed: beam collimation and sidelobe suppression. Therefore, according to the derived angular offset between the mainlobe direction and the beam axis, we steer the beam at the target through the phase shifter. Moreover, the sidelobe is suppressed by selecting an appropriate antenna pattern. Finally, based on the analysis of beam collimation and sidelobe suppression, we establish the CFDA configuration for beamforming. Numerical examples and simulations show the superiority of the proposed beamforming method.